Sustainable water solutions:a Six Sigma approach to membrane-based filtration system design - Usman, Ahmed; Khan, Haris; Tariq, Rasikh; Atta, M. Shahrukh; Rehman, Abdul; Iqbal, M. Mubashir (Frontiers in Environmental Science, 2024)
Water contamination is a major problem nowadays which can not only be solved through technological innovations but also requires educational innovation. The contamination of water is caused by discharging harmful pollutants into the water. These harmful contaminants cause different diseases. The significance of water filtration has grown in recent years. The quality of water is affected majorly by residual waste, bacteria, and so on. Based upon these issues, the Six Sigma methodology is used in this research for the design of a portable filtration system. This methodology is based on five steps that align with the computational competencies involving abstraction, decomposition of problem, and algorithmic thinking. Initially, a questionnaire approach is used to identify the need for a portable water filter for potential users.The Quality Function Development (QFD) matrix is used to measure the user's needs. Based on the user's information, a decision matrix tool is being used in the Analyze stage. After this theoretical concept is generated, and selection is made among various options. The complete drawing was made in the design stage after several stages of concept generation and selection.Then a prototype is developed to conduct proof of concept testing. The hollow fiber membrane (HFM) that is being used is manufactured usually by melt spinning, dry spinning, and wet spinning. But usually, a wet spinning method is predominantly used for manufacturing hollow fiber membranes. Polymer liquid like polyvinyl chloride (PVC) is used for the manufacturing of membranes with other liquids in different ratios. The size of pores varies from 0.01 to 0.1 microns. The flux rate usually depends upon the volume, length, and size of the cartridge.Backwashing at regular intervals is done for the presentation of fooling due to the accumulation of solutes. This filtration system is also proficient in rejecting bacteria that are being found in water and soil. This is done by a coliform test that is being performed for bacteria.